2017
DOI: 10.1016/j.bone.2017.03.043
|View full text |Cite
|
Sign up to set email alerts
|

Tissue expression and source of circulating αKlotho

Abstract: αKlotho (Klotho), a type I transmembrane protein and a coreceptor for Fibroblast Growth Factor-23, was initially thought to be expressed only in a limited number of tissues, most importantly the kidney, parathyroid gland and choroid plexus. Emerging data may suggest a more ubiquitous Klotho expression pattern which has prompted reevaluation of the restricted Klotho paradigm. Herein we systematically review the evidence for Klotho expression in various tissues and cell types in humans and other mammals, and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
60
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 236 publications
(289 reference statements)
7
60
0
1
Order By: Relevance
“…Some studies using the RT‐PCR approaches showed low bands from cardiac Klotho expression and other studies reported an inability to detect Klotho in mouse heart (Faul et al., 2011; Ghosh, Murphy, Kishore, & Vaughan, 2013; Sato et al., 2015; Tacer et al., 2010; Yamauchi et al., 2016). However, in spite of the contradictions in the mRNA expression of Klotho in the heart tissue, on the protein level, it has been detected in the heart using the western blot techniques, at a similar molecular size to renal Klotho (Olauson, Mencke, Hillebrands, & Larsson, 2017). So, the heart could be regarded not only as a target of soluble Klotho, but also probably an organ that produces Klotho itself (Corsetti et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies using the RT‐PCR approaches showed low bands from cardiac Klotho expression and other studies reported an inability to detect Klotho in mouse heart (Faul et al., 2011; Ghosh, Murphy, Kishore, & Vaughan, 2013; Sato et al., 2015; Tacer et al., 2010; Yamauchi et al., 2016). However, in spite of the contradictions in the mRNA expression of Klotho in the heart tissue, on the protein level, it has been detected in the heart using the western blot techniques, at a similar molecular size to renal Klotho (Olauson, Mencke, Hillebrands, & Larsson, 2017). So, the heart could be regarded not only as a target of soluble Klotho, but also probably an organ that produces Klotho itself (Corsetti et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Klotho is an anti‐aging hormone involved in senescence, endogenous antioxidants, apoptosis and phosphate homeostasis (Kuro‐o et al., 1997; Kurosu et al., 2005). Kidney tubular epithelial cells are the main source of circulating Klotho (Olauson, Mencke, Hillebrands, & Larsson, 2017). We found that full‐length membranous Klotho (designated tissue Klotho) was significantly decreased in OWT kidney tissue by ~45%, and GPX1 TG did not prevent this decrease (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…1 Full-length alpha-Klotho is a single-pass transmembrane protein that exists in 2 forms, membrane and secreted Klotho, which have different functions. 2 The membrane form acts as a co-receptor for fibroblast growth factor-23 (FGF-23) and plays an important role in calcium-phosphate metabolism. 2,3 Soluble Klotho (called α-Klotho, with molecular mass 130-kDa) seems to function as a humoral factor with various biological effects, and it works independently of FGF-23 signaling.…”
mentioning
confidence: 99%
“…2 The membrane form acts as a co-receptor for fibroblast growth factor-23 (FGF-23) and plays an important role in calcium-phosphate metabolism. 2,3 Soluble Klotho (called α-Klotho, with molecular mass 130-kDa) seems to function as a humoral factor with various biological effects, and it works independently of FGF-23 signaling. 4 Among the pleiotropic actions that soluble Klotho is responsible for are tissue protection from oxidative stress, fibrosis and apoptotic stimuli; regulation of blood phosphate and vitamin D3 levels; and the activity of multiple cell surface calcium and potassium ion channels.…”
mentioning
confidence: 99%
See 1 more Smart Citation